Wideband Microstrip 90° Hybrid Coupler Using High Pass Network. (7th April 2014) - Chiu, Leung
Abstract : A wideband 90° hybrid coupler has been presented and implemented in planar microstrip circuit. With similar structure of conversional 2-section branch-line coupler, the proposed coupler consists of a lumped high-pass network but not the quarter wavelength transmission at the center. The values of all lumped elements were optimized to replace a quarter-wavelength transmission line with a phase inverter. To demonstrate the proposed concept, a 1-GHz prototype was fabricated and tested. It achieves 90% impedance bandwidth with magnitude of S 11 less than −10 dB. Within this bandwidth, more than 13 dB port-to-port isolation, less than 5.0 degree phase imbalance, and less than 4.5 dB magnitude imbalance are achieved, simultaneously. The proposed coupler not only achieves much wider bandwidth but also occupies less circuit area than that of the conversional 2-section branch-line coupler.